Povečanje energetskega izkoristka mikro hidroelektrarn z ustvarjanjem naravnih brzic kot alternativa jezovom - Kene, David (Trajnost, 2025)
Hydropower, which represents a third (33.8%) of renewable energy sources in Slovenia and produces nearly a tenth (8.6%) of the annual energy balance, is extremely destructive to the river ecosystem due to damming. Dams, while harnessing potential energy, also contribute to river flow regulation and flood safety. However, since fish ladders have proven ineffective in preserving fish species, dams have become insurmountable river barriers for the entire ecosystem, casting doubts on their label as a „sustainable energy source.“ As an alternative, sustainable energy solutions in the form of submersible mills (e.g., Waterotor) and turbines that rely solely on river flow are emerging. At a time when even a 1% improvement in energy efficiency represents a significant gain, nature-based solutions (NBS) combined with micro turbines could represent a sustainable energy source and restore river ecosystems.
Keywords: jez; NBS; rečni ekosistem; trajnostna hidroelektrarna